2014
DOI: 10.1037/hea0000062
|View full text |Cite
|
Sign up to set email alerts
|

Attitude–behavior consistency, the principle of compatibility, and organ donation: A classic innovation.

Abstract: The lack of attitude-behavior consistency in the organ donor domain can be partially explained by limited compliance with the principle of compatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 45 publications
5
49
0
1
Order By: Relevance
“…First, our data indicated that children with positive attitudes towards MW reported more MW during the SART than children with negative attitudes, which is consistent with previous studies conducted by the introspection task (Hurlburt, 1980). This result also supports the notion of attitude-behaviour consistency that attitudes should be strongly associated with behaviours (e.g., (De Houwer, Custers, & De Clercq, 2006;Siegel, Navarro, Tan, & Hyde, 2014;Swanson, Swanson, & Greenwald, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…First, our data indicated that children with positive attitudes towards MW reported more MW during the SART than children with negative attitudes, which is consistent with previous studies conducted by the introspection task (Hurlburt, 1980). This result also supports the notion of attitude-behaviour consistency that attitudes should be strongly associated with behaviours (e.g., (De Houwer, Custers, & De Clercq, 2006;Siegel, Navarro, Tan, & Hyde, 2014;Swanson, Swanson, & Greenwald, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Specific attitudes towards organ donor registration were examined using a modified five‐item, 7‐point semantic differential scale (Siegel, Navarro, Tan, & Hyde, ; α = .96). Each item asked participants to consider their attitudes toward registering as a donor.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…A three‐item, 7‐point Likert scale, ranging from very unlikely to very likely , was used to assess intentions to register as an organ donor. This scale, from Siegel and colleagues (), has demonstrated strong internal consistency (α = .97), and has previously been used on both traditional and MTurk samples. A composite score was calculated, with higher scores indicating greater intentions to register as an organ donor.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…These includeV but are not limited toVthe consistency of attitudes and behavior toward organ donation (Siegel, Navarro, Tan, & Hyde, 2014), adherence to clinical guidelines (Kortteisto, Kaila, Komulainen, Mäntyranta, & Rissanen, 2010;Puffer & Rashidian, 2004), health literacy (Pleasant, McKinney, & Rikard, 2011), and medication adherence (Sutton, 2011). As one example, a study with intensive care nurses showed that, when nurses' knowledge and attitudes related to bowel management for critically ill patients were improved, nurses were more likely to perform the bowel management practices dictated by the protocol (Knowles et al, 2015).…”
Section: Overviewmentioning
confidence: 97%